Scientific Discourse: Evolution of Theoretical and Methodological Approaches and Concepts - M. Yu. Mironova (Дискурс, 2023)
Introduction. The article presents the results of an analytical review of scientific papers reflecting the stages of formation and development of the theory of scientific discourse in Russian linguistics. The purpose of the article is to systematize and critically analyze approaches, concepts and methodological principles of the study of scientific communication in the aspect of its communicative-pragmatic, genre-stylistic, linguocognitive and linguocultural specifics.Methodology and sources. The paper is based on theoretical concepts in the field of discourse analysis, considering discourse as a type of social practice, as a methodology of corpus linguistics using software tools and quantitative methods to extract language structures from large arrays of texts. An overview of the existing empirical research base is given.Results and discussion. As a result of the review study, the evolution of approaches to scientific discourse is characterized, their chronological framework is determined, key concepts that influenced the modern understanding of scientific communication are identified (genre-stylistic, sociocultural, cognitive, linguocultural, pragmalinguistic, communicative-pragmatic approaches), modern interpretations of scientific discourse are analyzed and prospects for further research are outlined. It is shown that in the study of scientific discourse, the corpus methodology is today in demand and is used in its synchronic and diachronic description. The diachronic development of the English-language scientific discourse by the example of a scientific article genre is an extremely interesting issue, which, according to our data, has not been thoroughly studied before. That is why our further works will be devoted to its consideration.Conclusion. It is shown that despite the long and intensive study of scientific discourse in the scientific literature there is an insufficient number of works highlighting the trends in the development of scientific communication genres, which demonstrate a certain historical dynamics and changes in the collective consciousness. It is concluded that the discursivecorpus approach to the study of scientific discourse and the methods of corpus linguistics make it possible to objectively identify and describe dynamic processes in the field of written scientific communication caused by changing ways of knowledge transfer under the influence of changes in the socio-cultural context and intensive development of science.